Strengthening capacity, incentives and institutions for food safety in Ethiopia: Guide for hygienic and safe handling of meat in butcher houses in Addis Ababa - Amenu, Kebede; Keba, Abdi; Dinede, Getachew; Mekonnen, A.; Tola, A.; Abate, Gashaw T.; Hoffmann, Vivian; Grace, Delia; Hung Nguyen-Viet (International Livestock Research Institute, 2024)
A basic food safety manual targeted at meat handlers in butcheries in Addis Ababa, Ethiopia.